REALITAS PENGELOLAAN LINGKUNGAN PENDIDIKAN ANAK USIA DINI: STUDI LAPANGAN PADA LEMBAGA PENDIDIKAN FORMAL DAN NONFORMAL - Hasna Aullia Dini; Rohinah; Hibana; Wiwit Purnama Putri; Amala Diska Fuaddiana (Fakultas Tarbiyah Universitas Ibrahimy Situbondo, 2025)
The learning environment has a crucial role in supporting the growth and development process of early childhood. Educational theories emphasize the importance of learning spaces that are safe, comfortable, aesthetic, and able to stimulate various aspects of children's development. However, the results of field observations in several Early Childhood Education (PAUD) units show that the implementation of these principles is still far from ideal. This article aims to reveal the reality of managing the PAUD learning environment based on the results of direct observations, with a focus on spatial aspects, suitability of facilities, and children's involvement in the learning environment. The findings show that there is a gap between theory and practice caused by limited resources, lack of educator training, and minimal awareness of the importance of the environment as an element of learning. This study emphasizes the need for joint efforts in building a PAUD learning environment that truly supports children's needs, starting from the most basic foundations: understanding, awareness and commitment to the quality of learning environment management.